Monitoring of meteorological conditions in 30-min resolution in Kopcany, western Slowakia, 2018-2022 - Fontenla-Razzetto, Gabriela; Tavares Wahren, Filipa; Heilig, Dávid; Heil, Bálint; Kovacs, Gábor; Feger, Karl-Heinz; Julich, Stefan (In: Fontenla-Razzetto, G et al. (2022): Monitoring of sap flow, sap velocity, soil condition and meteorology in hybrid poplar plantations (Populus deltoides Bart. Ex Marsh x P.nigra L. "AF2") in Kopcany, western Slowakia, 2018-2022 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.951255, 2022)
This dataset contains measurements of global radiation, precipitation, air temperature, relative humidity, air pressure, wind speed and wind direction from the study area of the project Dendromass4Europe. The aim of the study was to determine the influence of meteorological and soil-related site conditions on tree transpiration rates in poplar short rotation coppices plantations. In June 2018 a meteorological station was installed. The measurements started in June 2018 with a resolution of 30 minutes until end of May 2022 (31.05.2022). Three poplar SRC stands were selected according to a gradient of groundwater accessibility: S5-N (higher groundwater level), S4-D (low groundwater level), and S2-F (fluctuating groundwater level). On each of the selected sites one soil profile was excavated and prepared for the installation of soil sensors. The meteorological station was located southwest from the experimental sites. The distance from the meteorological station to the experimental sites was: 9.56 km to site S5-N (higher groundwater table), 9.82 km to site S4-D (low groundwater level), and 6.57 km to site S2-F (fluctuating groundwater table).